Finding it on the Internet : the Internet Navigator's guide to search tools and techniques - Gilster, Paul, 1949- (New York : Wiley, 1996)
Explains how to formulate searches on the Internet and provides step-by-step explanations of major Internet tools including Netscape, Mosaic, WinWAIS, WSGopher, Wsarchie, Yahoo, WebCrawler, archie, Jughead, and Veronica.
Includes index.
Adult
Adult
Keywords: Internet; World Wide Web; Internet; World Wide Web